PENERAPAN MODEL PEMBELAJARAN BERBASIS MASALAH (PROBLEM BASED LEARNING) DALAM MENINGKATKAN HASIL BELAJAR SISWA MATERI SISTEM PERSAMAAN LINEAR DUA VARIABEL KELAS VIII B SMP NEGERI 5 KOTABARU TAHUN PELAJARAN 2019/2020 - Khasratul Jannah (STKIP Paris Barantai, 2020)
This type of research is classified as classroom action research (CAR). Classroom action research is an effort aimed at improving the learning process or solving problems faced in learning. This classroom action research was conducted for 2 cycles, each cycle consisting of four activity stages, namely the planning, implementation, observation and reflection stages. The subjects in this study were students of class VIII B for the 2019/2020 school year at SMP Negeri 5 Kotabaru with 28 students. Sources of data used in this study were teachers and students. Data collection techniques were carried out by observation and tests. The instruments used were teacher and student learning implementation observation sheets, and student learning outcomes tests. The data analysis methods used were quantitative and qualitative. The indicators of the success of this study are the results of the analysis of the observation of the implementation of learning by teachers and students in the learning process can reach an average percentage of ≥ 81%. the minimum completeness of learning outcomes in the cognitive domain is 70 and classically said to be successful. in learning if it can reach ≥80% of the total student score that is complete. Keywords: Problem Based Learning, Learning Outcomes